A Review on ESCO’s Challenges and Project Management as a Solving Tool - Waqar Tariq; Mohammad Lutfi Othman; Noor Izzri Abdul Wahab; Mansoor Ebrahim (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
The Energy Service Industry is now declared as a new source of growth for Malaysian Economy, many key players like MAESCO, Suruhanjaya Tenaga Energy Commission, KeTTHA and relevant ministries are working very hard on energy saving respective researches. There is a room for much more improvement in order to apply energy saving projects according to Malaysian environment .So far the application of project management principles are very rare in energy saving projects or in Malaysia termed as ESCO (Energy Service Company). This gives a way to synchronise project management techniques with respective implementations of energy saving projects focusing Malaysian infrastructure. In this article a review is conducted on new ways, techniques and procedures of project management and its synchronization with engineering needs especially electrical power conservation and saving projects. Moreover, the proposed research will also indicate the advancement or replacement of present system along with some advantages over our old system. A complete review is done on the background of ESCO its importance in energy saving also the relevancy of project manajement along with its basic princlples is discussed as to provide a solution for ESCO to comeover the chellenges in South East Asia generaly and in Malaysia specifically